2019
DOI: 10.1039/c8ra09186b
|View full text |Cite
|
Sign up to set email alerts
|

Various antibacterial mechanisms of biosynthesized copper oxide nanoparticles against soilborneRalstonia solanacearum

Abstract: Green synthesized CuONPs disturb cell metabolism, biofilm formation, physical motility and gene expression in Ralstonia solanacearum, thereby effectively controlling bacterial wilt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(45 citation statements)
references
References 70 publications
(88 reference statements)
2
43
0
Order By: Relevance
“…CuO NPs at a 50 µg/mL concentration significantly inhibited the growth of total oral bacteria, extracellular polysaccharide (EPS) production, and biofilm formation on the glass, acrylic dentures, and cultured human epithelial cells as models [ 100 ]. It has also been shown that CuO NPs’ inhibitory concentration on Ralstonia solanacearum biofilms is 125 and 250 µg/mL after an incubation period of 24 and 72 h [ 101 ]. Thus, it is evident that CuO NPs can be potentially effective against biofilms, as shown in different groups of microorganisms.…”
Section: Effects Of Metal Oxide Nps On Plankton Cells and Biofilmmentioning
confidence: 99%
“…CuO NPs at a 50 µg/mL concentration significantly inhibited the growth of total oral bacteria, extracellular polysaccharide (EPS) production, and biofilm formation on the glass, acrylic dentures, and cultured human epithelial cells as models [ 100 ]. It has also been shown that CuO NPs’ inhibitory concentration on Ralstonia solanacearum biofilms is 125 and 250 µg/mL after an incubation period of 24 and 72 h [ 101 ]. Thus, it is evident that CuO NPs can be potentially effective against biofilms, as shown in different groups of microorganisms.…”
Section: Effects Of Metal Oxide Nps On Plankton Cells and Biofilmmentioning
confidence: 99%
“…On the one hand, by comparison to silver (Xiu et al, 2012), one might assume that it is only soluble copper, not particles, that are antimicrobial. On the other hand, increased activities of copper-based nanoparticles, above and beyond just copper ion content, have been indicated (Chen et al, 2019;Raffi et al, 2010;Sarkar et al, 2012). Indeed, the issue of whether nanoparticles per se have specific activity against bacteria, remains unclear but important.…”
Section: Introductionmentioning
confidence: 99%
“…First, copper acts on a similar principle to silver, as it combines with the thiol groups of key microbial enzymes and inactivates their functions [ 97 ]. Second, the Cu + ion from cuprous oxide (Cu 2 O) forms complexes with the peptides found within the microbial membranes [ 98 ]. Third, the dissociation of Cu 2+ from cupric oxide (CuO) induces ROS generation, leading to disturbances in amino acid and nucleic acid biosynthesis and the associated biochemical processes, e.g., iron displacement from iron–sulfur clusters and zinc or other metal ions competition for protein binding sites, disruption of the microbial membrane, and blocking of cellular respiration [ 60 , 95 , 96 , 98 , 99 ].…”
Section: Inorganic Nanoparticles With Antimicrobial Propertiesmentioning
confidence: 99%